Treatment of spontaneous preterm labour with retosiban: a phase 2 proof‐of‐concept study. (1st June 2015) - Thornton, Steven; Miller, Hugh; Valenzuela, Guillermo; Snidow, Jerry; Stier, Brendt; Fossler, Michael J.; Montague, Timothy H.; Powell, Marcy; Beach, Kathleen J.
<x xml:space="preserve">Abstract</x> Aim The aim was to investigate the efficacy and safety of intravenous retosiban in women with spontaneous preterm labour. Methods This was a randomized, double‐blind, placebo‐controlled, phase 2 trial. Retosiban was administered intravenously for 48 h to women in spontaneous preterm labour between 300/7 and 356/7 weeks' gestation with an uncomplicated singleton pregnancy in an in‐patient obstetric unit. Outcome measures were uterine quiescence (primary endpoint), days to delivery, preterm delivery and safety. Results Uterine quiescence was achieved in 62% of women who received retosiban (n = 30) compared with 41% who received placebo (n = 34). The relative risk (RR) was 1.53 (95% credible interval [CrI] 0.98, 2.48; NS). Retosiban resulted in a significant increase in time to delivery compared with placebo (mean difference 8.2 days, 95% CrI 2.7, 13.74). This difference was consistent across all gestational ages. The proportion of preterm births in the retosiban and placebo groups was 18.7% (95% CrI 7.4%, 33.7%) and 47.2% (95% CrI 31.4%, 63.4%), respectively. The RR of preterm birth in women treated with retosiban was 0.38 (95% CrI 0.15, 0.81). There were no deliveries within 7 days in the retosiban group, but there were six (17.6%) births in the placebo group. The maternal, fetal and neonatal adverse events were comparable in the retosiban and placebo groups. Conclusions Intravenous administration of retosiban in women with spontaneous preterm labour was associated with a greater than 1 week increase in time to delivery compared with placebo, a significant reduction in preterm deliveries, a non‐significant increase in uterine quiescence and a favourable safety profile.